Coeliac disease and bone mineral density in adult female patients. Issue 5 (November 1995) - Pistorius, L R; Sweidan, W H; Purdie, D W; Steel, S A; Howey, S; Bennett, J R; Sutton, D R
Abstract : A cross sectional study was undertaken to examine the relationship between coeliac disease and bone mineral density. The 135 female coeliac patients registered on the database of the Department of Gastroenterology at Hull Royal Infirmary were approached by letter, advising them of a potential risk of osteoporosis and inviting them to undergo bone densitometry. A total of 81 registered women (60%) attended the Osteoporosis Laboratory, Princess Royal Hospital and underwent dual energy x ray absorptiometry at the lumbar spine (L2-L4) and femoral neck. Historical data relating to the time of diagnosis and adherence to a gluten free diet were obtained. A control group was selected from the local normal population and was first matched for height, weight, and menopausal status. Postmenopausal patients were then further matched to controls of equivalent menopausal age. In coeliac patients, bone mineral density expressed in g/cm2 as mean (SD) was significantly lower at the lumbar spine (1.076 (0.186)) than in the control group (1.155 (0.143), p < 0.001). This was also the case at the femoral neck (0.887 (0.142) versus 0.965 (0.127), p < 0.001). When the coeliac patients were stratified by menopausal status, it was found that femoral neck bone mineral density was significantly below control values in both premenopausal and postmenopausal women. Spinal bone mineral density exhibited a significant decrement only in the postmenopausal group. The age at diagnosis of coeliac disease and adherence to a gluten free diet did not influence bone mineral density at either hip or spine. These results confirm coeliac patients' higher risk of osteopenia. Coeliac disease should be added to the list of medical conditions which constitute an indication for bone densitometry in order that the individual risk of osteoporosis related fracture may be determined.